2018
DOI: 10.1371/journal.pone.0204568
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of incident nasopharyngeal carcinoma with exposure to air pollution

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a race-specific malignancy. The nasal cavity is the main entry point for air pollutants or poisonous gases into the human body. However, the risk of NPC in populations exposed to air pollution remains unknown.MethodsWe combined data from the Taiwan Air Quality Monitoring Database (TAQMD) and the Longitudinal Health Insurance Database (LHID) to assess the risk of NPC in a population exposed to air pollution.ResultsMultivariate analysis revealed positive trends for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
1
25
1
2
Order By: Relevance
“…For every 1% increase in NO 2 concentrations, the overall NPC incidence increases by at least 1.706%, and the overall NPC incidence growth rate increases by at least 5.598%. These findings are consistent with previous studies who reported that NO 2 displayed the strongest association with NPC incidence, or CBD (Cerebrovascular Disease) and CVD (Cardiovascular Disease) mortality, as compared to SO 2 and PM 10 [2,15]. The harmful effect of indoor air pollution can support our finding from another perspective: An increased NPC risk has been found associated with daily incense burning (Adjusted OR = 2.49, 95% CI: 1.33-4.66) in women, and the adjusted OR for daily burning with good ventilation (1.35, 95% CI: 0.92-1.98) is much lower than that with poor ventilation (2.08, 95% CI: 1.02-4.24) [45].…”
Section: Discussionsupporting
confidence: 93%
“…For every 1% increase in NO 2 concentrations, the overall NPC incidence increases by at least 1.706%, and the overall NPC incidence growth rate increases by at least 5.598%. These findings are consistent with previous studies who reported that NO 2 displayed the strongest association with NPC incidence, or CBD (Cerebrovascular Disease) and CVD (Cardiovascular Disease) mortality, as compared to SO 2 and PM 10 [2,15]. The harmful effect of indoor air pollution can support our finding from another perspective: An increased NPC risk has been found associated with daily incense burning (Adjusted OR = 2.49, 95% CI: 1.33-4.66) in women, and the adjusted OR for daily burning with good ventilation (1.35, 95% CI: 0.92-1.98) is much lower than that with poor ventilation (2.08, 95% CI: 1.02-4.24) [45].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies investigating the clinical effects of air pollution on different organ systems in the human body have been conducted [4,[7][8][9]11,53]. Using similar datasets, we have previously shown that CO and NO 2 were associated with AMD [11], dementia [53], and PD [9].…”
Section: Discussionmentioning
confidence: 84%
“…Primarily, lung cancer is considered the major severe disease caused by air pollution [1,2]. Notably, accumulating evidence shows that chronic exposure to air pollution is associated with not only respiratory diseases but also non-lung cancers [3,4] and cardiovascular [5,6], inflammatory [7,8], and neurodegenerative diseases [9,10] including age-related macular degeneration (AMD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Der Endpunkt Kanzerogenität wurde auch in epidemiologischen Studien und Metaanalysen analysiert [113][114][115][116][117]. Auch in diesen Studien ist die NO 2 -Konzentration als Marker für Verkehrsemissionen zu verstehen, so dass die zum Teil gefundenen signifikanten Assoziationen zu erhöhten NO 2 -Konzentrationen für die ursächliche Bewertung nicht herangezogen werden können.…”
Section: Mutagenität Und Kanzerogenitätunclassified